1983
DOI: 10.1055/s-2007-969996
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rat Heart Phosphodiesterase by some Rotenoids and Isoflavonoids

Abstract: Series of natural and semisynthetic rotenoids and isoflavonoids were studied for their inhibitory activity on cyclic AMP phosphodiesterase (PDE) in rat heart. Some of the compounds showed higher inhibitory activity than that of the most potent flavonoids. The chemical transformation of the starting natural compounds failed to increase their inhibitory potency. PDE inhibition was of a noncompetitive type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Five-micron-thick sections, including the epidermis, the dermis, and the subcutaneous panniculus carnosus muscle, were mounted on glass slides, dewaxed, rehydrated in distilled water, and stained with hematoxylin and eosin(HE). All subsequent analyses were performed by an experienced pathologist without knowledge (Petkov et al, 1983;Li et al, 1993). The results of present study using wound healing experiments in animal models, biochemical analysis of wound biopsy, and in vitro studies showed that three different compounds isolated from the fruits of Amorpha fruticosa L. have antibacterial activity and promote the healing of wounds.…”
Section: Histological Examinationmentioning
confidence: 69%
“…Five-micron-thick sections, including the epidermis, the dermis, and the subcutaneous panniculus carnosus muscle, were mounted on glass slides, dewaxed, rehydrated in distilled water, and stained with hematoxylin and eosin(HE). All subsequent analyses were performed by an experienced pathologist without knowledge (Petkov et al, 1983;Li et al, 1993). The results of present study using wound healing experiments in animal models, biochemical analysis of wound biopsy, and in vitro studies showed that three different compounds isolated from the fruits of Amorpha fruticosa L. have antibacterial activity and promote the healing of wounds.…”
Section: Histological Examinationmentioning
confidence: 69%
“…Fruticin showed an inhibitory effect on rat heart phosphodiesterase. Its activity was found to be greater than the inhibitory activity of potent flavonoids such as luteolin, kaempferol, quercetin (Petkov et al, 1983). Hypercoagulability in rabbits with experimentally induced atherosclerosis was inhibited by oral administration of fruticin (Aǐzikov et al, 1984).…”
Section: Fruticin Contentmentioning
confidence: 99%
“…Petkov et al(1981) and Nikaido et al(1982) have shown that flavonoids possess an inhibitory action on cyclic (c) AMP phosphodiesterase. Since inhibition of this enzyme is associated with an increase of CAMP, it has been suggested that this increase offers a basis for the explanation of the myolytic activity of flavonoids (Petkov et al 1983). On the other hand, it has been documented that phosphodiesterase, like many other enzyme systems, is regulated by the Ca2+-binding protein calmodulin (West 1982).…”
Section: M)mentioning
confidence: 99%